A retrospective outcome study of 42 patients with Chronic Fatigue Syndrome, 30 of whom had Irritable Bowel Syndrome. Half were treated with oral approaches, and half were treated with Faecal Microbiome Transplantation. (August 2019) - Kenyon, J.N.; Coe, Shelly; Izadi, Hooshang
Abstract: The gut microbiome comprises the community of microorganisms in the intestinal tract. Research suggests that an altered microbiome may play a role in a wide range of disorders including myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Methods: 42 participants with ME/CFS with Irritable Bowel Syndrome (IBS) were allocated into one of two groups, 21 were treated with standard oral approaches, which centred around various nutritional remedies, probiotics, prebiotics, dietary advice and lifestyle advice. The second group who had mostly failed using oral approaches, were treated with Faecal Microbiome Transplantation (FMT). Each patient received 10 Implants, each from a different screened donor, and the Implants were processed under anaerobic conditions. The transplant is delivered via a paediatric rectal catheter, which is inserted through the anus to reach the lower part of the sigmoid colon. The results were assessed on a percentage basis before and after treatment, 0% being no improvement, 100% being maximum improvement. An exact non-parametric Mann-Whitney (one-tailed) test was used to compare medians from those on FMT compared with those receiving oral approaches only. On clinical experience over many years, the only way to judge improvement in Chronic Fatigue Syndrome as there is no test for Chronic Fatigue Syndrome, is my clinical assessment. Results: The median for the FMT group was found to be significantly higher compared to the oral treatment group (Mann-Whitney U = 111.5, p = .003). Therefore, the FMT group improved to a greater extent (z = −2.761). Conclusion: This study shows that FMT is a safe and a promising treatment for CFS associated with IBS. Adequately powered randomised controlled trials should be carried out to assess the effectiveness of FMT in patients with CFS and IBS.